2016
DOI: 10.1016/j.jenvman.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Removal of azo dye by a highly graphitized and heteroatom doped carbon derived from fish waste: Adsorption equilibrium and kinetics

Abstract: a b s t r a c tA highly graphitized and heteroatom doped porous carbon was prepared from fish waste in the present study. The morphology and chemical composition of the resultant porous carbon were characterized by SEM-EDS, TEM, BET, XRD and Raman measurement. The prepared porous carbon was employed as an adsorbent for acid orange 7, a typical azo dye, removal from aqueous solution. The results showed that the porous carbon had ultrahigh surface area of 2146 m 2 /g, a high degree of graphitization structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…It was heated at a rate of 10 °C/min from room temperature to 700 °C under purified nitrogen (99.999%) flow of 100 mL/min. The carbonization step was held for 2 h at 700 °C [29]. Subsequently, the sample was transferred to a beaker containing 2 mol/L HCl, stirred for 1 h, then washed with deionized water and dried at 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…It was heated at a rate of 10 °C/min from room temperature to 700 °C under purified nitrogen (99.999%) flow of 100 mL/min. The carbonization step was held for 2 h at 700 °C [29]. Subsequently, the sample was transferred to a beaker containing 2 mol/L HCl, stirred for 1 h, then washed with deionized water and dried at 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Aliouche et al found that color removal caused by azo dyes followed an increasing order: UV < acetone/UV < S 2 O 8 2− /heat < S 2 O 8 2− /H 2 O 2 /UV < S 2 O 8 2− /UV < H 2 O 2 /UV [ 9 ]. Various nanomaterials used as the absorbents contain cobalt-zinc ferrite nanoadsorbents [ 19 ], silica nano-composite [ 16 , 20 , 21 , 22 ], nano zero-valent iron [ 23 ], Fe 3 O 4 nano-composite [ 24 , 25 , 26 , 27 ], carbon nanomaterials [ 28 , 29 , 30 , 31 , 32 , 33 ] and clay [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…and pose serious problems, even in minute concentrations (Ferhat et al, 2016). More than 8000 chemical products are associated with the dyeing process with 2% of the annually produced dyes (Almost 10 9 kg, 70% of which are azo dyes) discharged directly in aqueous effluents (Fanun, 2014;Liu et al, 2016;Salvi and Chattopadhyay, 2016). Amongst these azo dyes, Orange II (OII) is one of the most widely used reactive dyes in the textile dyeing industries (Heibati et al, 2015).…”
mentioning
confidence: 99%